2015
DOI: 10.1016/j.tube.2015.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Two positive tuberculosis cases in the late Nigrovits family, 18th century, Vác, Hungary

Abstract: Mycobacterium tuberculosis V ac Hungary Mummies Paleopathology Paleomicrobiology s u m m a r y Two mummies of the Hungarian mummy collection from V ac were the subjects of anthropological, paleopathological, radiological, paleomicrobiological, paleohistological and paleoproteomic studies. Both individuals belonged to the same family. The father, J ozsef Nigrovits (No 29), died at the age of 55 on the 11th of November 1793; his son, Antal Nigrovits (No 54), died on the 16th of July 1803, at the age of 22. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Molecular studies confirmed TB in ancient human remains from necropoles in Ancient Egypt [78], Asia [79,80], America [81][82][83][84], and Europe [77,[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100]. These authors reported aDNA extracted and analyzed and positively tested for MBTC, both from vertebral lesions and highly associated lesions.…”
Section: Established and Emerging Techniques For Molecular Studiesmentioning
confidence: 96%
“…Molecular studies confirmed TB in ancient human remains from necropoles in Ancient Egypt [78], Asia [79,80], America [81][82][83][84], and Europe [77,[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100]. These authors reported aDNA extracted and analyzed and positively tested for MBTC, both from vertebral lesions and highly associated lesions.…”
Section: Established and Emerging Techniques For Molecular Studiesmentioning
confidence: 96%
“…The combined application of morphology, aDNA and lipid biomarker analysis is important to gain a clearer picture in paleopathological practice as the results can support each other, and help to reveal positive cases, which would possibly remain hidden if only one method was applied (Hershkovitz et al 2008;Lee et al 2012;Baker et al 2015;Masson et al 2015;Molnár et al 2015;Donoghue et al 2017;Luna et al 2020). The examination of mummified human remains with a variety of different approaches is especially useful and provides a unique insight to TB research (Salo et al 1994;Zink et al 2003;Donoghue et al 2004;Donoghue et al 2009;Minnikin et al 2011;Chan et al 2013;Lalremruata et al 2013;Kay et al 2015;Piombino-Mascali et al 2015;Szikossy et al 2015). Verification of TB infection in mummified human remains…”
Section: Váradi Et Almentioning
confidence: 99%
“…Most of these individuals lived in the 18th century CE, which is from the pre-antibiotic era; therefore, they represent a well-characterised link between recent and archaeological samples. Besides the broad pathological investigations, demographical analysis and exploration of family connections were carried out, as well as attempts to reconstruct individual life stories (Kustár et al 2011a(Kustár et al , 2011bSzikossy et al 2015;Szikossy 2020).…”
mentioning
confidence: 99%
“…In our opinion, dry bone histology is best used to corroborate the diagnosis of infection, and to determine its location, extent and developmental phase [also see De Boer et al (2013b)]. For the identification of specific pathogens, the recent advances in the application of molecular techniques are promising (Donoghue et al, 1998;Kolman et al, 1999;Donoghue et al, 2004;Zink et al, 2005a;Hershkovitz et al, 2008;Redman et al, 2009;Keller et al, 2012;Szikossy et al, 2015;Fournier et al, 2015;Maixner et al, 2016).…”
Section: Infectious Diseasesmentioning
confidence: 99%